Les genres récrits n° 4 - Daniel Elmiger (Glad!)
This chronicle focuses on the violent controverse happened in France about "inclusive writing". Daniel Elmiger sheds light on polemic, by contrasting it with the Swiss situation, in terms of language planning as well as in terms of studies and proposals. The author concludes by outlining the necessity to overstep the opposition between basic pro and contra stances in order to collectively build concrete and substantial solutions, suitable for a broad range of texts, including official and institutional texts in French.